2021
DOI: 10.1002/pamm.202100236
|View full text |Cite
|
Sign up to set email alerts
|

Using Deep Learning to Enhance Compton Camera Based Prompt Gamma Image Reconstruction Data for Proton Radiotherapy

Abstract: Proton beam radiotherapy is a cancer treatment method that uses proton beams to irradiate cancerous tissue while simultaneously sparing doses to healthy tissue. In order to optimize radiational doses to the tumor and ensure that healthy tissue is spared, many researchers have suggested verifying the treatment delivery through real-time imaging. One promising method of real-time imaging is through a Compton camera, which can image prompt gamma rays emitted along the beam's path through the patient. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Our results show that it is in fact feasible to apply a fully connected neural network to this problem. Further tests as well as discussions of the effect classification has on actual reconstructions are provided in [3].…”
Section: Results: Classifying a Complete Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that it is in fact feasible to apply a fully connected neural network to this problem. Further tests as well as discussions of the effect classification has on actual reconstructions are provided in [3].…”
Section: Results: Classifying a Complete Eventmentioning
confidence: 99%
“…We propose that a neural network can be trained to determine if a given event is "false" or, if true, the correct camera interaction ordering. A more complete discussion is available in [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our initial studies in [28] showed that our general NN configuration is capable of identifying both true and false triple scatters. In this study, we have expanded the complexity of the Frontiers in Physics frontiersin.org network to now consist of 64 residual blocks with eight fully connected layers per block yielding a total of 512 hidden layers.…”
Section: Neural Network Training and Validation Performancementioning
confidence: 98%
“…This more complex network, as shown in these results, is able to handle more complex triple scatter datasets, that include true and false events, as well as DotT and false triples. Similar to [28], all data used for training and validation are simulated and are produced by the MCDE model discussed in Section 2.1.1. We use an 80/ 20 training/validation data split as is suggested in [15] but since our data is entirely simulated this split is arbitrary and done for consistency with other research within the domain.…”
Section: Neural Network Training and Validation Performancementioning
confidence: 99%
“…These problems make the reconstructed PG depth profile more noisy and unusable in clinical use (Polf and Parodi 2015). Therefore, several research groups have proposed machine learning-based event selection as a worthwhile approach to reduce background in Compton camera imaging (Barajas et al 2021, Muñoz et al 2021, Polf et al 2022 and deliver more precise doses to the tumors during proton therapy (Gueth et al 2013, Basalyga et al 2020. To evaluate the performance of our Compton camera prototype currently under investigation, a machine learning software based on the ROOT (Brun and Rademakers 1997) toolkit for multivariate data analysis 'TMVA' (Hoecker et al 2007) is proposed to properly discriminate Compton events from background events.…”
Section: Introductionmentioning
confidence: 99%